Temporal dominance of sensations, emotions, and temporal liking measured in a bar for two similar wines using a multi‐sip approach. Issue 5 (25th July 2018) - Silva, Ana P.; Voss, Hans‐Peter; van Zyl, Hannelize; Hogg, Tim; de Graaf, Cees; Pintado, Manuela; Jager, Gerry
Abstract: Eating and drinking are dynamic processes where both sensations and emotions might evolve or change over time during multiple bites/sips. However, most previous studies have measured food‐evoked emotions statically, that is, at a fixed time point after consumption and using a single bite/sip approach. This study aimed to explore the sensitivity of temporal dominance of sensations (TDS), of emotions (TDE), and temporal liking (TL), using a multi‐sip approach, to differentiate between two comparable tasting wines. A glass of wine, in an appropriate consumption context, a bar, was served to 69 consumers, in two different sessions. It was shown that TDS and TDE captured small differences between equally liked wines. Wines were distinguishable during consumption, based on the dominance of basic sensations such as acid, bitter, and dry, rather than aromatic sensations and based on three emotions pleased, comforted, and relaxed. These emotions were dominant in both wines and in all stages of consumption but differed in the dominance rates. So, the impact of wine consumption on emotions was more uniform during consumption while new sensations became dominant during drinking. Practical implications: The method tested in this study showed a sensitivity level sufficient to capture subtle but significant differences between similar, equally liked wines. Wines tested have a major difference in wine‐making process, that is, one of the wines had a particular wood aging processing in new oak barrels conferring specific flavors and associated costs. For the wine industry, the method can be particularly useful to understand to which extent consumers perceive differences in sensations and emotions, in a blind tasting, to investigate if increased costs of production are acceptable and justified. For other food products, the method can be useful to use during product development stage, when the aim is to differentiate prototypes with subtle differences in ingredients composition and associated costs. Knowing when certain sensations and emotions occur during consumption might help to create successful products in the market. Further research using different food or beverages is however necessary to assure its validity.